The Bureau : Inside Today's FBI - Jeffreys, Diarmuid (London Macmillan, 1994)
An explosive investigation into America's primary law enforcement agency, the FBI, written with an insider's knowledge of its agents and documents.
Include Index
Keywords: United States. Federal Bureau of Investigation -- Federal Bureau of Investigation